Miroring Movie: A Rampant Phenomenon on the Tiktok APP - Rahmatullah, Zidane Nur; Mustofa, Imron (Syiar Hukum, 2024)
This study examines the mirroring of movies on TikTok, a rising issue that challenges copyright enforcement in Indonesia. Using a normative juridical approach, it evaluates the effectiveness of Law No. 28 of 2014 and Government Regulation No. 71 of 2019 in tackling digital piracy. Despite existing regulations, enforcement remains weak due to difficulties in identifying infringers, user anonymity, rapid content dissemination, and limited enforcement mechanisms. TikTok’s reactive content moderation relies on user reports rather than proactive detection, delaying the removal of infringing content. Cross-border legal complexities further hinder enforcement. This study suggests AI-driven content detection, stricter platform accountability, stronger government oversight, and enhanced collaboration between stakeholders. Public awareness campaigns on digital copyright are also essential. Strengthening these aspects will lead to a more effective copyright protection framework in Indonesia’s digital landscape.